Characterization of the β-defensin genes in giant panda - Zhang, Zhi-Yi (Sci Rep, 2018)
β-Defensins are small antimicrobial proteins expressed in various organisms and have great potential for improving animal health and selective breeding programs. Giant pandas have a distinctive lineage in Carnivora, and it is unclear whether β-defensin genes have experienced different selective pressures during giant panda evolution. We therefore characterized the giant panda (Ailuropoda melanoleuca) β-defensin gene family through gap filling, TBLASTN, and HMM searches. Among 36 β-defensins identified, gastrointestinal disease may induce the expression of the DEFB1 and DEFB139 genes in the digestive system. Moreover, for DEFB139, a significant positive selection different from that of its homologs was revealed through branch model comparisons. A Pro-to-Arg mutation in the giant panda DEFB139 mature peptide may have enhanced the peptide’s antimicrobial potency by increasing its stability, isoelectric point, surface charge and surface hydrophobicity, and by stabilizing its second β-sheet. Broth microdilution tests showed that the increase in net charge caused by the Pro-to-Arg mutation has enhanced the peptide’s potency against Staphylococcus aureus, although the increase was minor. We expect that additional gene function and expression studies of the giant panda DEFB139 gene could improve the existing conservation strategies for the giant panda.